Allergen immunotherapy for the prevention of allergy: A systematic review and meta‐analysis. Issue 1 (12th December 2016) - Kristiansen, Maria; Dhami, Sangeeta; Netuveli, Gopal; Halken, Susanne; Muraro, Antonella; Roberts, Graham; Larenas‐Linnemann, Desiree; Calderón, Moises A.; Penagos, Martin; Du Toit, George; Ansotegui, Ignacio J.; Kleine‐Tebbe, Jörg; et al.
Abstract: Background: There is a need to establish the effectiveness, cost‐effectiveness, and safety of allergen immunotherapy (AIT) for the prevention of allergic disease. Methods: Two reviewers independently screened nine international biomedical databases. Studies were quantitatively synthesized using random‐effects meta‐analyses. Results: A total of 32 studies satisfied the inclusion criteria. Overall, meta‐analysis found no conclusive evidence that AIT reduced the risk of developing a first allergic disease over the short term (RR = 0.30; 95% CI: 0.04–2.09) and no randomized controlled evidence was found in relation to its longer‐term effects for this outcome. There was, however, a reduction in the short‐term risk of those with allergic rhinitis developing asthma (RR = 0.40; 95% CI: 0.30–0.54), with this finding being robust to a pre‐specified sensitivity analysis. We found inconclusive evidence that this benefit was maintained over the longer term: RR = 0.62; 95% CI: 0.31–1.23. There was evidence that the risk of new sensitization was reduced over the short term, but this was not confirmed in the sensitivity analysis: RR = 0.72; 95% CI: 0.24–2.18. There was no clear evidence of any longer‐term reduction in the risk of sensitization: RR = 0.47; 95% CI: 0.08–2.77. AIT appeared to have an acceptable side effect profile. Conclusions: AIT did not result in a statistically significant reduction in the risk of developing a first allergic disease. There was, however, evidence of a reduced short‐term risk of developing asthma in those with allergic rhinitis, but it is unclear whether this benefit was maintained over the longer term. We are unable to comment on the cost‐effectiveness of AIT.